Role of Haridra as an Anti-Depressant (AYUSHDHARA, 2025)
Depression is characterized by decreased interest in daily activities, irritation and low concentration for extended periods. It is the leading causes of disability and 2nd leading cause of death (by suicide) in world with a prevalence rate of 5% of the world’s adult population according to World Health Organization. However, due to stigma, a lack of effective treatments, and a dearth of mental health resources, it is frequently misdiagnosed and untreated. Haridra also identified as Curcuma Longa in Latin is one of the Ayurvedic drug which can be pivotal in treatment in depression as well as easily available, cost effective in long run with virtually no side effects. Curcumin present in Haridra is proven to be effective antidepressant. It is effective in regulating the levels of neurotransmitters, insulin resistance, oxidative and nitrosative stress, hypothalamic-pituitary-adrenal disruptions, and modulate inflammatory pathways, excitotoxicity, neuroplasticity and the endocannabinoid system. We will go over Haridra’s effects through its phytoconstituent curcumin and how it affects the etiopathogenesis of depression in this review.